Pengembangan Perangkat Pembelajaran IPA Model Inkuiri Terbimbing (Guided Inquiry) untuk Meningkatkan Pemahaman Konsep Siswa SMP - Fery Hermanto; Soetjipto Soetjipto; M. Thamrin Hidayat (IKIP Mataram, 2016)
The objective of this research to produced learning materials were valid, practical, and effective to improved student’s conceptual understanding. The development of learning material used the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model and was tried out at VIII-A and VIII-B on SMP Negeri 1 Bandung Tulungagung with One Group Pretest-Posttest Design. Data were collected by used observation method, tests, and questionnaires. Data was analyzed descriptive analysis quantitatively and qualitatively. The results showed that 1) the learning material are valid categorized; 2) learning material in terms of practical category in (a) feasibility of instruction good category, (b) Obstacles for learning could be overcome, (c) student’s activity was active category; (3) the learning material effectiveness in terms of; (a) The response of student’s positively, and (b) student’s conceptual understanding increased significant after learning material was tried out. It could be concluded that the intervention design was valid, practical and effective to improved student’s learning achievement.